AN ANALYSIS OF THE HISTORY OF BRAZIL BY THE POLITICAL ECONOMY OF WORLD-SYSTEMS - Vieira, Rosangela de Lima [UNESP] (Univ Feevale, Inst Ciencias Sociais Aplicadasicsa, 2018)
The present study intends to demonstrate that the analysis of the Political Economy of the World-Systems ( PEWS) has significant contributions a reflection of the current Brazilian reality. The PEWS develops its approach from the systemic perspective, whose basic elements are: a long-term historical analysis; interdisciplinarity; the interrelations between political, economic, social and cultural aspects; and the international division in center, semiperiphery and periphery. The main purpose of the article is to make explicit that our history over five centuries is of subordination to the interests of the center of capitalist accumulation. Although the center has been moving over these centuries, the peripheral condition most of the time and semiperiphery in shorter temporal durations persists. The traditional view of history, though often attempting to seek the interests of capital in the relations between the Iberians and colonies / ex-colonies, did not allow a more comprehensive look at this historical reality. In turn, PEWS's approach innovates the analysis of Brazilian history, showing, for example, the interrelations between: the Great Navigations and the hegemony of Italian cities; colonization and Dutch interests; British political emancipation and business; the establishment of the Brazilian republican period and the transition from British hegemony to North American.
Keywords: Brazil; Political economy of World-Systems; Periphery; Semiperiphery